ALTERNATIF PAKAN TERNAK BERGIZI DAN BERNUTRISI DENGAN MEMANFAATKAN LIMBAH PERTANIAN DI DESA JELU NGASEM - Amanda, Herliana; Budiana, Aldi Setia; Alifa, Nurul Fatmawati; Herdriyani, Diva Ferliana; Rahmadhini, Faradilla Ayu; Ghozi, Ahmad Syaiful; Elvania, Nindy Callista (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Jelu Village is one of the villages in Ngasem District, Bojonegoro Regency, with residents whose main livelihood is farmers and livestock breeders. Making fermented animal feed as a form of utilising existing agricultural waste. The objectives to be achieved with this work program for making fermented animal feed include introducing the concept of animal feed fermentation and the benefits it can provide, as well as providing knowledge about appropriate technology in improving the nutritional quality of animal feed to the Jelu Village Community. In implementing the animal feed work program, the method used is Knowledge Transfer or transfer of knowledge with counselling and training in making fermented animal feed, which has two stages: Education or socialisation and Assistance in making fermented animal feed. It can be said that the people of Jelu Village have been greatly helped by the manufacture of alternative fermented feed and the use of abundant agricultural waste.